Destruction caused by greed and brutality as reflected in Shakespeare’s Macbeth: A psychological approach - Nuri Fainuddin (Universitas Ahmad Dahlan)
Destruction Caused by Greed and Brutality as Reflected in Shakespeare’s Macbeth: A Psychological Approach becomes the title of the research. It is intended to describe the greed and brutality of the main character; the main character’s id, ego, and super ego; the catastrophe suffered by the main character, and the moral values of this drama. The subject of the research is Macbeth, a play written by William Shakespeare and the main character’s greed. The object is the psychological aspect of the main character. The research belongs to a library research since its sources are taken from books. Horney’s theory of greed is applied to analyze the data. The study found several interesting results. First, Macbeth becomes a king by murdering King Duncan (a form of Macbeth’s greed). Second, Macbeth’s brutality is shown by murdering Banquo’s and Macduff’s family. Third, Macbeth’s id is murdering the king and the followers; the ego supports the King; and the super ego cuts of the King head when Birnam wood comes. The play delivers several messages to the readers, such as those who plant will harvest and the good deed will destroy the bad deed.